Fe3O4@HKUST-1 and Pd/Fe3O4@HKUST-1 as magnetically recyclable catalysts prepared via conversion from a Cu-based ceramic. Issue 29 (8th June 2017) - Toyao, Takashi; Styles, Mark J.; Yago, Tokuichiro; Sadiq, Muhammad M.; Riccò, Raffaele; Suzuki, Kiyonori; Horiuchi, Yu; Takahashi, Masahide; Matsuoka, Masaya; Falcaro, Paolo
Abstract : A Fe3 O4 /Cu- ceramic system converted into a magnetic HKUST-1 composite was used as a recyclable catalyst for one-pot cascade and hydrogenation reactions. Abstract : Nanocomposites obtained by integrating iron oxide magnetic nanoparticles (Fe3 O4 ) into a metal–organic framework (HKUST-1 or Cu3 (BTC)2, BTC = 1, 3, 5-benzenetricarboxylate) are synthesized through conversion from a composite of a Cu-based ceramic material and Fe3 O4 . In situ small-angle X-ray scattering (SAXS) and wide-angle X-ray scattering (WAXS) measurements reveal that the presence of Fe3 O4 leads to the fast conversion and synthesis of HKUST-1 with small particle sizes. The prepared MOF composite (Fe3 O4 @HKUST-1) is found to catalyze the one-pot sequential deacetalization–Knoevenagel condensation reaction as a magnetically collectable and recyclable catalyst. In addition, Pd nanoparticles are also incorporated into the material (Pd/Fe3 O4 @HKUST-1) by addition of a Pd colloidal solution during the conversion of the precursor composite to HKUST-1. The resulting Pd/Fe3 O4 @HKUST-1 can be utilized for hydrogenation of 1-octene in the liquid phase.